BCG-Induced Cross-Protection and Development of Trained Immunity: Implication for Vaccine Design - Covián, Camila; Fernández-Fierro, Ayleen; Retamal-Díaz, Angello; Díaz, Fabián E.; Vasquez, Abel E.; Lay, Margarita K.; Riedel, Claudia A.; González, Pablo A.; Bueno, Susan M.; Kalergis, Alexis M. (Frontiers in Immunology, 2019)
The Bacillus Calmette-Guérin (BCG) is a live attenuated tuberculosis vaccine that has the ability to induce non-specific cross-protection against pathogens that might be unrelated to the target disease. Vaccination with BCG reduces mortality in newborns and induces an improved innate immune response against microorganisms other than Mycobacterium tuberculosis, such as Candida albicans and Staphylococcus aureus. Innate immune cells, including monocytes and natural killer (NK) cells contribute to this unspecific immune protection in a way that is independent of memory T or B cells. This phenomenon associated to a memory-like response in innate immune cells is known as “trained immunity”. Epigenetic reprogramming through histone modification in the regulatory elements of particular genes has been reported as one of the mechanisms associated to the induction of trained immunity in both, humans and mice. Indeed, it has been shown that BCG vaccination induces changes in the methylation pattern of histones associated to specific genes in circulating monocytes leading to a "trained" state. Importantly, these modifications can lead to the expression and/or repression of genes that are related to increased protection against secondary infections after vaccination, with improved pathogen recognition and faster inflammatory responses. In this review, we will discuss the BCG-induced cross-protection and acquisition of trained immunity and potential heterologous effects of recombinant BCG vaccines.